A hydrostatic pressure-driven passive micropump enhanced with siphon-based autofill function. Issue 15 (22nd June 2018) - Wang, Xiaolin; Zhao, Da; Phan, Duc T. T.; Liu, Jingquan; Chen, Xiang; Yang, Bin; Hughes, Christopher C. W.; Zhang, Weijia; Lee, Abraham P.
Abstract : We present a micropump enhanced with siphon-based autofill function to realize autonomous and continuous perfusion with steady flow over extended time. Abstract : Autonomous and self-powered micropumps are in critical demand for versatile cell- and tissue-based applications as well as for low-cost point-of-care testing (POCT) in microfluidics fields. The hydrostatic pressure-driven passive micropumps are simple and widely used, but they cannot maintain steady and continuous flow for long periods of time. Here, we propose a hydrostatic pressure-driven passive micropump enhanced with siphon-based autofill function, which can realize the autonomous and continuous perfusion with well-controlled steady flow over an extended time without electric power consumption. The characterization results reveal that both the cycle number in one refilling loop and the siphon diameter will affect the refilling time. Furthermore, this micropump also enables multiplexed medium delivery under either the same or different flow conditions with high flexibility. The system was validated using an in vitro vasculogenesis model over the course of several days. Most importantly, the device can consistently provide steady medium perfusion for up to 5 days at a predefined hydrostatic pressure drop without the need for supplemental medium changes. We believe that this hydrostatic pressure-driven passive micropump will become a critical module for a broad range of sophisticated microfluidic operations and applications.